2015
DOI: 10.1089/tmj.2014.0221
|View full text |Cite
|
Sign up to set email alerts
|

Can We Trust the Use of Smartphone Cameras in Clinical Practice? Laypeople Assessment of Their Image Quality

Abstract: Whereas one smartphone camera ranked best more often, all three smartphones obtained results at least as good as those of the digital camera. Smartphone cameras can be a substitute for digital cameras for the purposes of medical teleconsulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…In line with recent research showing that images of quality can be taken with a smartphone, 14 our results support the notion that handheld devices are a good solution for image-based teleconsultation. The ratings addressed in this study are however limited to a small number of images and it might be that handheld devices are more suitable for occasional advice than for a high load of pictures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with recent research showing that images of quality can be taken with a smartphone, 14 our results support the notion that handheld devices are a good solution for image-based teleconsultation. The ratings addressed in this study are however limited to a small number of images and it might be that handheld devices are more suitable for occasional advice than for a high load of pictures.…”
Section: Discussionsupporting
confidence: 92%
“…consultation. Concerning quality, the participants were asked to rank order the importance of five image features: 14 focus, resolution, contrast, colour and composition and then how they interpreted the word 'quality' when completing the survey. Demographic data were collected at the very end.…”
Section: Surveymentioning
confidence: 99%
“…Initial assessments within the current project showed that the quality of images taken at point of care with smartphone cameras is good enough to be used for diagnostic support. The results showed that both size and depth of burns could be assessed at least as well using photographs as at bedside and that the image quality of handheld devices can be used as well as computers [18,19]. There are several challenges that need to be considered when evaluating the potential health impact of the system.…”
Section: Discussionmentioning
confidence: 99%
“…of objects, people or situations) are perceived by laypeople when taken by different smartphone cameras as opposed to being taken with a digital camera (all taken by a specialist photographer) [18]. The results showed wide variations among raters (60 people in total) for any given image and camera but a relatively good level of satisfaction.…”
Section: Follow-up Design and Outcome Measuresmentioning
confidence: 99%
“…Although our protocol allowed an outpatient visit by patients in the TM group at any time, diabetologists did not feel confident enough with the TM system to include more patients. This problem of image quality and the limits to the use of pictures sent by TM was recently stressed in literature (4,5).…”
mentioning
confidence: 99%